REMAJA, LIKE, DAN IDENTITAS: PERSONAL BRANDING DI DUNIA DIGITAL - Sisca Aulia; Keira Djauwvanka Kurniawan; Kathline Alexandra Thedianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
Personal branding is a strategic process for recognizing, shaping, and conveying a positive and authentic self-image to the social environment. The phenomenon of personal branding among adolescents has experienced significant growth with the increasing use of social media as a space for expression and identity formation. A community service activity conducted at Yakobus High School aimed to analyze how adolescents utilize digital platforms like Instagram, TikTok, and YouTube to build a socially recognized self-image. Through a systematic literature review approach, this activity examines the dynamics between self-presentation, social media algorithms, and the psychosocial impacts that arise from personal branding practices. The results of this activity indicate that adolescents use visual curation strategies, persona consistency, and digital storytelling to gain social validation through metrics such as